Rules and Roles vs. Consensus: Self-Governed Deliberative Mass Collaboration Bureaucracies. (May 2013) - Joyce, Elisabeth; Pike, Jacqueline C.; Butler, Brian S.
Deliberative mass collaboration systems, such as Wikipedia, are characterized as undisciplined, unstructured social spaces where individuals participate in collective action. However, examination of Wikipedia reveals that it contains a bureaucratic structure, which ensures that collective goals are primary drivers of that collective action. To support large-scale activity, deliberative mass collaboration systems must provide ways of reconciling the tension between individual agency and collective goals. Wikipedia's unusual policy, ignore all rules (IAR), serves as this tension release mechanism. IAR supports individual agency when positions taken by participants might conflict with those reflected in established rules. Hypotheses are tested with Wikipedia data regarding individual agency, bureaucratic processes, and IAR invocation during the content exclusion process. Findings indicate that in Wikipedia each utterance matters in deliberations, rules matter in deliberations, and IAR citation magnifies individual influence but also reinforces bureaucracy.